2019
DOI: 10.1016/j.ajog.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Levonorgestrel intrauterine system associated amenorrhea: a systematic review and metaanalysis

Abstract: Objective Data Amenorrhea is a polarizing noncontraceptive effect of the levonorgestrel intrauterine system. Composite amenorrhea prevalence estimates that summarize all clinical data for the first-year after insertion currently are not available. The purpose of this study was to investigate the validity of existing prevalence estimates by the systematic calculation of amenorrhea measures for a general population of levonorgestrel intrauterine system users and to provide 90-day interval point esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Overall, although women's experiences varied, patterns of contraceptive-induced bleeding changes were consistent in our study with what has been reported for each long-acting reversible contraceptive in other studies. 21 , 22 , 23 In general, side-effects are a key cause of discontinuation in sub-Saharan Africa. 24 Although the Demographic and Health Surveys did not until recently differentiate between bleeding changes and non-bleeding side-effects, other available evidence suggests that bleeding changes can be particularly problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, although women's experiences varied, patterns of contraceptive-induced bleeding changes were consistent in our study with what has been reported for each long-acting reversible contraceptive in other studies. 21 , 22 , 23 In general, side-effects are a key cause of discontinuation in sub-Saharan Africa. 24 Although the Demographic and Health Surveys did not until recently differentiate between bleeding changes and non-bleeding side-effects, other available evidence suggests that bleeding changes can be particularly problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Amenorrhea was defined as the complete absence of bleeding for 3 months, as defined by the World Health Organization and used in many contraception trials, including a recent systematic review and metaanalysis of amenorrhea with levonorgestrel IUD use. 16,17 We considered a patient amenorrheic if they reported no current bleeding or spotting and no bleeding in the 3 months preceding the visit. If they were amenorrheic for the majority of the year but had some current or recent bleeding, they were not considered amenorrheic.…”
Section: Methodsmentioning
confidence: 99%
“…Most users experience spotting and irregular bleeding initially, but such irregularities may reduce over time, and some users may experience a pause in bleeding with these methods. [45][46][47] The copper IUD typically results in heavier periods. 48 Changes to menstrual bleeding patterns represent an important reason for discontinuation and non-use of contraception.…”
Section: Menstrual Disordersmentioning
confidence: 99%